UV-assisted autolysis for nutrient bioconversion of sea cucumber (Stichopus horrens) body wall - Umam, Nada Itorul; Sulaiman, Alifdalino; Yong, Foo Wong; Jaya-Ram, Annette; Sau, Pinn Woo; Zulkurnain, Musfirah (Springer, 2023)
Enzymatic hydrolysis is a green approach for nutrient bioconversion of sea cucumber body wall to recover sulfated polysaccharides. However, formation of high level of advanced glycation end products (AGEs) can potentially negate health benefits of the functional food. In this study, UV-assisted autolysis was employed to optimize nutrient bioconversion of Stichopus horrens body wall using extreme UV dosage (324,000-648,000 J/m2), different autolysis temperatures (40–60 °C) and time (3–5 h). Parallel biochemical changes indicate that UV irradiation promoted the activation of endogenous enzymes, leading to the proteolysis of the body wall and the subsequent dissolution of sulfated polysaccharides. Changes in the amide band I region of the Fourier-transform infrared (FTIR) spectra of autolyzed body wall residue reflected the loss of α-helix secondary structures of collagen which exacerbated at autolysis temperatures beyond 50 °C. The maximum yield of sulfated polysaccharides and antioxidant activities were obtained at the condition (486,000 J/m2 of UV dosage, 60 ℃, and 4 h of autolysis) by the optimization using the central composite design. The nutritional composition and safety aspect of the autolysate was compared with hydrolysate from enzymatic hydrolysis and hot water extract. Quantification of 5-hydroxymethylfurfural (HMF) showed that UV-assisted autolysis could mitigate HMF formation (0.12 mg/kg) by 97.6% compared to enzymatic hydrolysis (5.13 mg/kg) and 42.9% compared to hot water extraction (0.21 mg/kg). The UV-assisted autolysis with metal ion further enhanced the extraction process of sulfated polysaccharides from sea cucumber body wall and reduction of the processing contaminants. Thus, UV-assisted autolysis offers a safer alternative for the nutrient bioconversion of sea cucumber body wall, particularly for the development of functional foods.